2016
DOI: 10.1111/mcn.12307
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stunting reduction in Ethiopia 2000 – 2011

Abstract: The prevalence of stunting in Ethiopia declined from 57% in 2000 to 44% in 2011, yet the factors producing this change are not fully understood. Data on 23,999 children 0-59 months of age from three Demographic and Health Surveys (DHS) from 2000, 2005, and 2011 were analyzed to assess the trends in stunting prevalence, mean height-for-age z-scores (HAZ) and the associations between potential factors and HAZ. Associations were determined separately using three separate generalized linear models for children age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…In contrast, Jones et al () observed a significantly lower HAZ in children exclusively breastfed from 0 to 6 months of age. In our analysis of pooled DHS data from 2000, 2005 and 2011 (Woodruff et al ), exclusive breastfeeding was not associated with HAZ. Regarding early cessation of breastfeeding, WHO recommends that children be breastfed up to 2 years of age or beyond (World Health Organization et al ).…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…In contrast, Jones et al () observed a significantly lower HAZ in children exclusively breastfed from 0 to 6 months of age. In our analysis of pooled DHS data from 2000, 2005 and 2011 (Woodruff et al ), exclusive breastfeeding was not associated with HAZ. Regarding early cessation of breastfeeding, WHO recommends that children be breastfed up to 2 years of age or beyond (World Health Organization et al ).…”
Section: Resultsmentioning
confidence: 57%
“…Low maternal education has been associated with higher levels of stunting in children 6–23 months of age in southern Ethiopia (Agedew & Chane ) and among children 0–59 months in an analysis of Ethiopia's DHS data from 2000 and 2005 (Alemayehu & Huang ). Our pooled analysis of Ethiopia's 2000, 2005, and 2011 DHS data did not find any association between maternal education and HAZ in children 0–23 months of age, but maternal education was significantly associated with child growth in children 24–59 months, and improvements in maternal education since 2000 were associated with reductions in stunting for this age group (Woodruff et al ). Results were mixed for parental literacy's influence on linear growth.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Along with poor prior health and immunization status, decreased access to basic needs such as food, water, shelter, and sanitation, we found the study community under high risk of contracting various infectious diseases and subsequent death. Furthermore, infectious diseases can also exacerbate malnutrition [18]. This destructive needs to be broken with appropriate food and nutritional support for the drought affected households, treatment of malnourished children as well as preventing and rapidly treating disease conditions.…”
Section: Discussionmentioning
confidence: 99%